(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The economic prosperity of a country mostly hinges on the presence of enough infrastructure and construction within its vicinity. Substructures facilitate the connection between individuals and essential services, markets, and employment opportunities, hence promoting the well-being and productivity of individuals. Transportation is a crucial component of infrastructure that enables the movement of goods and individuals between different locations. The passengers have high expectations from Indian railroads, yet, the railroads only provide a limited number of services in good quality, while many of its services are subpar. When the Indian Railways fails to meet passengers’ expectations, they are prepared to transition to an alternative form of transportation. In recent years, the passenger business earnings of Indian Railways have declined, with the railway freight services playing a significant part in contributing to the overall railway earnings. The current study aims to identify the various services offered by the Southern Railway and explore ways in which the railway may enhance its services to better meet the needs of its customers. This involves aligning the service offerings with the demands and preferences of rail users. The study examines the comprehensive range of services and amenities supplied by the Southern Railway (SR), as well as the degree of satisfaction among passengers and their suggestions for enhancing the services and facilities offered by the Southern Railway. The current study aims to identify the various services offered by the Southern Railway and explore strategies for enhancing these services to better meet the demands of customers and train users, aligning them with the railway’s service offerings. Passenger satisfaction with the southern railway hinged on the quality of service and the quality of rail services.